Sustentabilidade e saúde pública: relatos médicos sobre patologias associadas ao uso de agrotóxicos - o caso do Município de Marechal Cândido Rondon PR - Vanderlinde, Juliane (2016)
Because of the hegemonic model of food production, thousands of people are poisoned by pesticides. Poisonings increase each year, particularly in areas where uses pesticides. It is known that there are enough studies to prove that pesticides damage the health of farm workers and residents of nearby towns to agricultural regions, causing acute intoxication, subacute and chronic, and triggering a serious public health issue in Brazil. This is a research of a qualitative nature where interviews were carried out with medical that are references in the municipality of Marechal Candido Rondon and had the objective of analyzing the relation of diseases with the use of pesticides. The doctors interviewed dominated the subject with experiences of years experienced in the city and, in addition to reporting on diseases related to pesticides, were discussed poisoning cases that were neglected and the influence of the capitalist system that overlaps the quality of life of the human. Due to acute poisoning by pesticides, cases of abortions, preterm births, malformations and hypospadia in babies newborns, were reported by the physicians interviewed as a frequent diseases in the population. The professionals also draw attention to neoplasms in general and depression as clinical pathologies related to the use of agrochemicals in chronic form. It is concluded that the medical support for the diagnosis of diseases, the correct use of personal protective equipment for the application of pesticides and a existence of protocols within Public Health programs aimed at the continuous monitoring of the rural worker would be some protective actions in search of resolution of the problem with regard to contamination by the use of pesticides